Adiponectin and resistin modulate the progression of Alzheimer's disease in a metabolic syndrome model - Cisternas, Pedro; Gherardelli, Camila; Gutierrez, Joel; Salazar, Paulina; Mendez-Orellana, Carolina; Wong, G. William; Inestrosa, Nibaldo C. (My University, 2023)
Metabolic syndrome (MetS), a cluster of metabolic conditions that include obesity, hyperlipidemia, and insulin resistance, increases the risk of several aging-related brain diseases, including Alzheimer's disease (AD). However, the underlying mechanism explaining the link between MetS and brain function is poorly understood. Among the possible mediators are several adipose-derived secreted molecules called adipokines, including adiponectin (ApN) and resistin, which have been shown to regulate brain function by modulating several metabolic processes. To investigate the impact of adipokines on MetS, we employed a diet-induced model to induce the various complications associated with MetS. For this purpose, we administered a high-fat diet (HFD) to both WT and APP/PSN1 mice at a pre-symptomatic disease stage. Our data showed that MetS causes a fast decline in cognitive performance and stimulates A beta(42) production in the brain. Interestingly, ApN treatment restored glucose metabolism and improved cognitive functions by 50% while decreasing the A beta(42/40) ratio by approximately 65%. In contrast, resistin exacerbated Ab pathology, increased oxidative stress, and strongly reduced glucose metabolism. Together, our data demonstrate that ApN and resistin alterations could further contribute to AD pathology.
Keywords: adiponectin; resistin; obesity; alzheimer ' s disease; glucose metabolism